2010
DOI: 10.1073/pnas.1000985107
|View full text |Cite|
|
Sign up to set email alerts
|

Different amygdala subregions mediate valence-related and attentional effects of oxytocin in humans

Abstract: The neuropeptide oxytocin enhances the processing of positive social stimuli and improves the capacity to effectively attend the eye region of conspecifics. To investigate the neural basis of these effects, we combined intranasal oxytocin administration with high-resolution functional magnetic resonance imaging in a unique emotion classification task. Emotional faces were briefly presented while controlling for the initial fixation, and measuring subsequent eye movements. Oxytocin had differential effects on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

49
438
15
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 452 publications
(508 citation statements)
references
References 51 publications
49
438
15
6
Order By: Relevance
“…Notably, OT administration effects were lateralized to the left amygdala, although the same (albeit non-significant) directionality of effects was observed in the right amygdala. In line with our findings, OT administration effects in left amygdala reactivity toward emotional faces have been found in healthy males (Gamer et al, 2010;Kirsch et al, 2005), healthy females (Domes et al, 2010) and male patients with Asperger's syndrome (Domes et al, 2014). On the other hand, OT administration effects on right-sided amygdala reactivity toward emotional faces has also been observed in healthy males (Domes et al, 2007;Petrovic et al, 2008), females with and without BPD (Bertsch et al, 2013) and males with Asperger's syndrome (Domes et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Notably, OT administration effects were lateralized to the left amygdala, although the same (albeit non-significant) directionality of effects was observed in the right amygdala. In line with our findings, OT administration effects in left amygdala reactivity toward emotional faces have been found in healthy males (Gamer et al, 2010;Kirsch et al, 2005), healthy females (Domes et al, 2010) and male patients with Asperger's syndrome (Domes et al, 2014). On the other hand, OT administration effects on right-sided amygdala reactivity toward emotional faces has also been observed in healthy males (Domes et al, 2007;Petrovic et al, 2008), females with and without BPD (Bertsch et al, 2013) and males with Asperger's syndrome (Domes et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Although OT administration has predominantly been found to dampen amygdala reactivity (eg, Domes et al, 2007;Kirsch et al, 2005;Petrovic et al, 2008), increased amygdala reactivity has also been observed after OT administration. OT administration resulted in enhanced amygdala reactivity toward happy faces in healthy males (Gamer et al, 2010), and toward fearful (Domes et al, 2010) and angry faces (Bertsch et al, 2013) and threatening scenes (Lischke et al, 2012) in healthy females. In addition, increased amygdala reactivity toward neutral faces was observed after OT administration in male patients with Asperger's syndrome (Domes et al, 2013(Domes et al, , 2014.…”
Section: Discussionmentioning
confidence: 94%
“…The sequence of OXT and PLA sessions was counter-balanced across subjects. We adopted a standardized protocol used in previous studies (Gamer et al, 2010;Labuschagne et al, 2010) where participants selfadministered a single intranasal dose of 24 IU OXT/PLA (three puffs per nostril, each puff with 4 IU, or 6.82 mg) under the supervision of the experimenter 45 min before each fMRI scanning session. Participants abstained from alcohol during the 24 h and from exercise, caffeine, and food for 1 h before the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Inhaled OT increases gaze toward the eye region of faces in humans (8,10,11) and increases the frequency and duration that rhesus macaques look at other monkeys (4). However, OT may not generally enhance social attention, but instead may bias social attention.…”
mentioning
confidence: 99%
“…One possible mechanistic explanation for these complex effects is that OT may alter social attention, which would necessarily adjust the information available for social perception and decision making (4,5,(8)(9)(10). Inhaled OT increases gaze toward the eye region of faces in humans (8,10,11) and increases the frequency and duration that rhesus macaques look at other monkeys (4).…”
mentioning
confidence: 99%